2016
DOI: 10.19128/turje.30206
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness Level and Future Expectations of Gifted Students

Abstract: Some characteristics of gifted students may affect their view of the future positively, but some of them may have a negative influence. Therefore, the aim of the present study is to explore future hope and expectations among gifted middle school students. A mixed method was used for this research. Beck Hopelessness Scale and Positive Future Expectations Scale were administered to 65 gifted (41 boys and 24 girls) middle school students. In order to collect the qualitative data, content analysis of these gifted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…Similarly, in different studies, supporting the results of this study, it has been found that students perceive the future as promising and enlightening (Topgül, 2017;Yam, Çetinkaya & Kurnaz, 2018). In Oğurlu's (2016) research done to determine hopelessness and future expectation in gifted middle school students, it was found that gifted students had a positive future orientation and they were not hopeless.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…Similarly, in different studies, supporting the results of this study, it has been found that students perceive the future as promising and enlightening (Topgül, 2017;Yam, Çetinkaya & Kurnaz, 2018). In Oğurlu's (2016) research done to determine hopelessness and future expectation in gifted middle school students, it was found that gifted students had a positive future orientation and they were not hopeless.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…Several studies have been conducted in the literature on the future in Turkey and worldwide. In the Turkish literature, researchers have conducted studies on topics such as the adaptation of scales (Avcı & Erden, 2009;Summak Gören, 1998), university students' perceptions of the future (Avcı, 2008;Avcı & Erden, 2013;Bayav, 2018;Gümüşgil et al, 2016;Kocadağ & Bardakçı, 2016), the study of university students' attitudes toward the future (Büyüktopçu, 2017), the level of hopelessness and future expectations among gifted students (Ogurlu, 2016), and university students' future anxiety (Kocaman & Kuybu-Rol, 2020;Tayfun et al, 2022). A review of the international literature has identified studies on various aspects of the future, including future time perspective (Fingerman & Perimutter, 1995;Peetsma, 2000;Bembenutty & Karabenick, 2004;Husman & Shell, 2008;Bilde et al, 2011;De Lange et al, 2011;Coudin & Lima, 2011;Allemand et al, 2012;Brothers et al, 2014;Henry et al, 2017;Kooij et al, 2018;Lucija, 2018;Büyük & Çelik, 2020), the relationship between future planning and life satisfaction (Azizli et al, 2015), the present perception and future vision of gifted students (Krneta, 2016), and future orientation (Gjesme, 1975;Gjesme, 1979;Gjesme, 1983;Holman & Silver, 2005;Carstensen & Lang, 2006;Hortsmanshof & Zimitat, 2007;Joireman et al, 2012;Carmi, 2013;Joireman & Liu, 2014;…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gifted students are an opportunity to accelerate the development of our country, and their work in their field can make our country more independent in economic, political, and many ways. Gifted students are considered as students with the potential to shape the future (Ogurlu, 2016). However, in our country, the career path of gifted students are not followed.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that no study has been done on issues such as how these individuals contribute to society after their graduation, their future expectations, and what are the future expectations of the society on these individuals. When the future perspective is considered as a variable that increases the current success of the individual (Lens & Rand, 2000), researches on this subject show that the perspective is important for the future success of the individuals (Ogurlu, 2016). Besides, it is stated that the future perspectives and passions of gifted children directly affect their hopeful situation (Lovecky, 1992, cited in Ogurman, 2016.…”
Section: Introductionmentioning
confidence: 99%